Los celtas y la onomástica. El caso hispano (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
Classical sources place Hispano-celtic population in both Southwestern and Galician regions, apart from Celtiberia; the epigraphic distribution of the nomina gentilicia formed with the -icus suffix (that is to Celtics’ liking) agrees with these areas.
Keywords: Celtic; Hispania; Onomastics; Personal Names, -icus Suffix; Nomina Gentilicia